Preparation and characterization of fermented based coconut extract (Cocos Nucifera) with cajá pulp (Spondias Mombin L) (Research, Society and Development, 2023)
The high incidence of individuals with allergies, food intolerance and those who choose not to use food of animal origin as a lifestyle, causes them to exclude milk and derivatives from their diet, a behavior that can lead to nutritional deficiencies. To avoid deficits, the demand for substitutes for cow's milk was increased. Thus, plant extracts emerge as promising replacements. The objective of this research was to develop a fermented drink based on coconut with cajá pulp, to analyze it physicochemically, microbiologically and to evaluate its potential for substituting the fermented milk base. The coconut extract was prepared and then the preparation of the probiotic drink was carried out, after fermentation, the cajá pulp was added to one of the formulations. The products were evaluated for physical-chemical parameters (pH, total acidity, water content, total dry extract, fixed mineral residue, soluble solids and lipids), viability of microorganisms and microbiological quality. It was found that the fermented products met the physicochemical requirements established for such food, in addition to having shown probiotic potential by containing lactic acid bacteria exhibiting values greater than 106 CFU/mL, and absence of total coliforms, molds and yeasts. Furthermore, a lack of specific legislation for fermented vegetables was identified. It was observed that the elaboration of the fermented drink can positively influence the commercialization of probiotic and lactose-free products, so that the fermented product demonstrates good physical-chemical and microbiological characteristics. However, still needing to be tested for sensory and technological analysis of the product class.